Generalized Ostrowski inequalities and computational integration - Nazia Irshad; Asif R. Khan; Hina Musharraf (Journal of Numerical Analysis and Approximation Theory, 2020)
We state and prove three generalized results related to Ostrowski inequality by using differentiable functions which are bounded, bounded below only and bounded above only, respectively. From our proposed results we get number of established results as our special cases.